1999
DOI: 10.1046/j.1523-1755.1999.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

α8 Integrin in glomerular mesangial cells and in experimental glomerulonephritis

Abstract: These results show that in human, rat, and mouse glomeruli, alpha8 integrin is strongly and exclusively expressed in MCs. Gene expression of alpha8 is regulated in cultured MCs, and alpha8 protein abundance is regulated in vivo and in MC culture. It is currently unclear what functional properties this integrin receptor protein has with regard to MC anchorage to extracellular matrix and modulation of the MC phenotype in normal and diseased glomeruli. However, in view of its abundance in the mesangium, alpha8bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 21 publications
3
83
1
Order By: Relevance
“…Mesangial cells express a broader range of ␤ 1 integrins, including (25,31,32), and most ␣-specific antagonists affected adhesion of these cells to the TSRs. This suggests that the TSRs are pan-specific ligands for ␤ 1 integrins.…”
Section: Figmentioning
confidence: 99%
“…Mesangial cells express a broader range of ␤ 1 integrins, including (25,31,32), and most ␣-specific antagonists affected adhesion of these cells to the TSRs. This suggests that the TSRs are pan-specific ligands for ␤ 1 integrins.…”
Section: Figmentioning
confidence: 99%
“…Rabbit polyclonal antiserum to ␣8 integrin was used at a dilution of 1:500, as described previously (4). Monoclonal antibodies to ␣-smooth muscle actin and proliferating cell nuclear antigen (PCNA) (both from Dako Diagnostika, Hamburg, Germany) were used at a dilution of 1:500, after blocking of endogenous mouse IgG with a MOM kit (Linaris, Wertheim, Germany).…”
Section: Antibodiesmentioning
confidence: 99%
“…In the adult kidney, ␣8 expression was noted in glomeruli and renal arterioles (3). In immunohistochemical studies, we demonstrated that glomerular expression of ␣8 was restricted to the mesangium in human, rat, and mouse kidneys (4). ␣8␤1 is a receptor for fibronectin, vitronectin, tenascin-C (5), osteopontin (6), and a novel ligand termed nephronectin (7).…”
mentioning
confidence: 99%
“…Existent evidence indicates a link between a8b1 integrin expression and cardiac, lung, kidney and liver fibrosis. [12][13][14] When we look at the pathological conditions in which a8 expression is increased, we see that there is one property in common. In these fibrotic organs, tensile forces are increased.…”
Section: Tensegrin In Contextmentioning
confidence: 99%
“…13 Stellate cells of the liver, lung alveolar myofibroblasts, and lung interstitial cells are other cell types with intense a8 integrin leads to reduced membrane-anchored RhoA, a hallmark of RhoA activity 51 ( Fig. 2A).…”
Section: Lessons From Parallel Universesmentioning
confidence: 99%